Association between low first trimester maternal serum PAPP-A levels and presence of unilateral or bilateral uterine artery diastolic notches - Fırat Tülek; Ali Gemici; Alper Kahraman (Perinatal Medicine Foundation, 2021)
Objective Uterine artery impedance is known to have an effect on first trimester aneuploidy screening biomarkers. In this study we aim to compare first trimester screening parameters in women with and without uterine artery diastolic notches. Methods This retrospective case control study was conducted in a single tertiary center by obtaining medical records of women that admitted for first trimester pregnancy follow-up. Singleton pregnancies without structural anomalies, chromosomal anomalies and obstetric complications were included in the study. 268 women with first trimester unilateral uterine artery diastolic notches are constituted study group 1, 149 women with bilateral uterine artery diastolic notches constituted study group 2. 200 women were randomly selected as control group. Results Significantly decreased PAPP-A levels were found in both study groups. PAPP-A levels were even lower in women with bilateral notches in comparison to unilateral notches. Fetal birth weights and gestational ages at birth were also found significantly lower in study groups. Beta human chorionic gonadotropin levels and nuchal translucency measurements were found similar. Prevalence of false positive first trimester aneuploidy screening test results were significantly higher in women with bilateral uterine artery diastolic notches. Conclusion Presence of first trimester uterine artery diastolic notches, particularly the presence of bilateral diastolic notches, is related with decreased PAPP-A levels in first trimester aneuploidy screening and lead to higher false positive rates in first trimester aneuploidy screening and consequently more unnecessary invasive procedures.